Television sports production - Owens, Jim 1957- (Routledge, 2021)
"In this sixth edition of Television Sports Production, regional Emmy Award-winning producer Jim Owens walks readers through the planning, set-up, directing, announcing, shooting, and editing involved in covering a sports event. Originally written as a training guide for entry level broadcast staff at the Olympics, this manual gives readers the tools they need to effectively cover sports from ice skating to motorcycle racing. Throughout, Owens breaks down all aspects of the production process, revealing the techniques that producers and directors use to bring sports to a worldwide audience. Chapters further include tips and advice on using the latest technologies and tools such as production trucks, REMIs, smart phones, mobile units, cameras, audio equipment, and lighting rigs. Featuring new instructive illustrations and sample forms, as well as testimonials from experienced professionals in the business, this new edition gives readers an inside look at how the experts produce live or recorded television and sports coverage. This comprehensive book is essential reading for intermediate and advanced students looking to learn how to successfully produce sports broadcasting"--